Building to Learn/Learning to Build - Sergio Palleroni (Oz, 2006)
There is a crisis in the architectural profession and in architectural education. Architects are beginning to lose control over the building process. Interior designers have taken over design of the building from within, engineers have begun to offer complete building design services, and builders now incorporate design services into their repertoire.